REAL-world evidence of risk factors and comorbidities in YOUNG Indian adults with type 2 diabetes mellitus: A REAL YOUNG (diabetes) study - Saboo, Banshi; Agarwal, Sanjay; Gupta, Sunil; Makkar, Brij; Panneerselvam, A; Sahoo, Abhay; Ramchandani, G; Das, Sambit; Erande, Suhas; Kadam, Yogesh; Abhyankar, Mahesh; Revankar, Santosh (Journal of family medicine and primary care, 2021)
Objective: To assess the clinical characteristics, risk factors, and comorbidities associated with type 2 diabetes mellitus (T2DM) in young adult patients. Methods: This is a retrospective, multicentric real-world study that included young adults (18-45 years) with T2DM. Primary information including demographics, medical and family history, biochemical measures (pre-and post-prandial blood glucose levels, glycosylated hemoglobin [HbA1c] and blood pressure, and lipid parameters) smoking and drinking habits were collected retrospectively from the medical records of the respective hospitals/clinics. Data were analyzed using descriptive and appropriate comparative statistics. Results: A total of 22,921 patients from 623 sites were included. The median age was 37.0 years and the majority were men (61.6%). The proportion of patients from the age group >35-≤45 years was 62.7%. Among all patients, 46.9% had only T2DM; however, 53.1% of patients had T2DM with other comorbidities (T2DM with hypertension, dyslipidemia, and both). The majority of patients had elevated body mass index (BMI) (overweight, 46.6%; and obese, 22.9%). Family history of T2DM (68.1%) was most common in overall population. Sedentary lifestyle (63.1%), alcohol consumption (38.9%), and regular smoking (23.1%) were the most common associations in patients with T2DM with dyslipidemia and hypertension. Uncontrolled HbA1c level (≥7%) were observed in 79.2% of patients. The level of HbA1c was significantly increased with the duration of T2DM and sedentary lifestyle (p < 0.001). Conclusion: Higher BMI, family history of T2DM, sedentary lifestyle, alcohol consumption, and smoking were the most common risk facors, while hypertension and dyslipidemia were the most prevalent comorbidities associated with T2DM in young Indian adults.